Factors influencing appetite and depression among institutionalised Chinese Elderly in Penang - Suzana Shahar,; Yow, Bee Charn (Penerbit UKM, 2009)
Poor appetite and inadequate food intake together with depression are associated with malnutrition, that will increase risk of morbidity and mortality among elderly people. Identifying factors associated with these conditions are essential for formulation of preventive strategies. Therefore, a study was conducted to identify factors associated with poor appetite and depression among institutionalised Chinese elderly people in Butterworth, Penang. A total of 100 Chinese elderly (49 men and 51 women) aged 60 years and above, (mean age ± SD of 74.7 ± 9.2 years), with no known terminal and mental illnesses from two nursing homes participated in this study. Subjects were interviewed to gather information on appetite using Council of Nutrition Appetite Questionnaire (CNAQ), depression using Geriatric Depression Scale(GDS) and also socio demographic and health status. Food intake was assessed using a combination of one-day food weighing and 24 hour diet recall. Body weight and height were measured. Results showed that the mean energy and nutrients intake did not achieve the Recommended Nutrient Intake of Malaysia (RNI), with the exception for vitamin C. Only 4% of the subjects were underweight and obese, 65% normal and 31% overweight. A total of 70% and 73% of subjects had poor appetite and depression, respectively. Subjects who had depression (adjusted OR = 2.78, 95% CI = 0.95-8.03), energy intake below RNI (adjusted OR = 2.34, 95% CI = 0.68-6.95) and difficulty to fall asleep at night (insomnia) (adjusted OR = 2.22, 95% CI = 0.72-6.82) were more likely to have poor appetite. Subjects who had poor appetite (adjusted OR = 3.36, 95% CI = 1.19-9.47) and insomnia (adjusted OR = 2.58, 95% CI = 0.83-7.98) were more likely to have depression. In conclusion, although the majority of subjects had normal body weight but the nutrient intake was inadequate. Poor appetite and depression were prevalent and interrelated and also strongly associated with insomnia.